Advanced glycation end products of dietary origin and their association with inflammation in diabetes – A minireview - Pedreanez Adriana; Robalino Jorge; Tene Diego; Salazar Patricio (Endocrine Regulations, 2024)
Advanced glycation end products (AGEs) are a diverse group of compounds that are formed as a result of the non-enzymatic reaction between a reducing sugar such as glucose and the free NH2 groups of an amino acid in a protein or other biomolecule. The chemical reaction, by which these products are generated, is known as the Maillard reaction and occurs as a part of the body’s normal metabolism. Such a reaction is enhanced during diabetes due to hyperglycemia, but it can also occur during the preparation, processing, and preservation of certain foods. Therefore, AGEs can also be obtained from the diet (d-AGE) and contribute to an increase of the total serum pool of these compounds. They have been implicated in a wide variety of pathological processes, mainly because of their ability to induce inflammatory responses and oxidative stress increase. They are extensively accumulated as a part of the normal aging, especially in tissues rich in long half-life proteins, which can compromise the physiology of these tissues. d-AGEs are abundant in diets rich in processed fats and sugars. This review is addressed to the current knowledge on these products and their impact on the immunomodulation of various mechanisms that may contribute to exacerbation of the diabetes pathophysiology.